2012
DOI: 10.1258/ar.2011.110136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diffusion parameters and T2 values of the masseter muscle during jaw opening, clenching, and rest

Abstract: The eigenvalues for diffusion of the MM were sensitive to jaw position. The recruitment of muscle fibers, specific to jaw position, reflects the differences in changes in muscle diffusion parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Thereafter, it was hypothesized that changes in joint position, which lead to muscle shortening or lengthening, would lead to changes in muscle architecture and therefore in DTI parameters as well. For the ankle this was addressed in several studies, of which six reported values for the tibialis anterior muscle and five dealt with the medial gastrocnemius muscle. Changes in DTI parameters were linked to increased cell diameter in shortened muscles, changes in extra and intracellular fluids, and postexercise effects (Table ).…”
Section: Feasibility Studies and Reported Variances In Healthy Skeletmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, it was hypothesized that changes in joint position, which lead to muscle shortening or lengthening, would lead to changes in muscle architecture and therefore in DTI parameters as well. For the ankle this was addressed in several studies, of which six reported values for the tibialis anterior muscle and five dealt with the medial gastrocnemius muscle. Changes in DTI parameters were linked to increased cell diameter in shortened muscles, changes in extra and intracellular fluids, and postexercise effects (Table ).…”
Section: Feasibility Studies and Reported Variances In Healthy Skeletmentioning
confidence: 99%
“…" (19-21, 24, 110, 112) # (21) " (20,24) 5 (21) # (19,110,111) Increased/decreased cell diameter in shortened/elongated muscles. Changed composition in extra and intracellular fluids.…”
Section: Muscle Elongationmentioning
confidence: 99%
“…They concluded that MTC imaging strongly reflected edematous changes in masseter muscle, possibly related to masseter muscle myalgia. Shiraishi et al examined changes in the diffusion parameters of the masseter muscles in 11 healthy volunteers during jaw opening and clenching on diffusion-tensor imaging [36]. Ariji et al assessed edematous changes in the masseter muscles of 10 healthy volunteers caused by low-level static contraction on T2-weighted interactive decomposition of water and fat with echo asymmetry and least-square estimation (IDEAL) water images [37].…”
Section: Resultsmentioning
confidence: 99%
“…In the recent years, studies using MRI and sonography in patients with masticatory muscle myalgia have frequently been reported, and the newly developed technologies have been introduced [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38]. Muscles after treatment in those patients also have been evaluated using MRI and sonography [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted imaging and diffusion tensor imaging methods can be used to evaluate changes that accompany skeletal muscle contraction [119]. The coefficients for diffusion of the masseter muscles are sensitive to change by clenching—one possible cause of TMDs [120].…”
Section: Myositis and Muscle Edema/contracture-related Myofascial Paimentioning
confidence: 99%